1979
DOI: 10.3181/00379727-161-40508
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Calcium Absorption in the Rat with Experimental Diabetes

Abstract: We previously studied downhill calcium absorption in the diabetic rat (luminal concentration 3.4 mM, serum ionized calcium, 1-1.1 mM): Duodenal absorption by diabetics was half that of controls whereas ileal absorption was normal (1). Although vitamin D intake and absorption of fat are normal in diabetic rats (l), we subsequently found vitamin D metabolism to be abnormal: serum concentrations of 1,25-dihydroxyvitamin D (1,25-(OH),D) in diabetics are one-eighth the levels in controls (2). Since 1,25-(OH)2D is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The finding of normal [24] or low [25, 261 serum immunoreactive parathyroid hormone concentration in serum from insulin treated diabetics, and high urinary excretion rates of calcium [25,261 favour the hypothesis that the bone mineral loss is due to a primary disturbance in bone metabolism [24,251 rather than secondary to a renal loss of calcium which would lead to secondary hyperparathyroidism [27]. Normal intestinal calcium absorption has been reported in a few human diabetics [24,28], whereas low or absent calcium absorption in the duodenum was found in diabetic rats [29]. In a few studies serum I ,25-dihydroxyvitamin D has been measured and was found to be normal [24] or decreased [30].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of normal [24] or low [25, 261 serum immunoreactive parathyroid hormone concentration in serum from insulin treated diabetics, and high urinary excretion rates of calcium [25,261 favour the hypothesis that the bone mineral loss is due to a primary disturbance in bone metabolism [24,251 rather than secondary to a renal loss of calcium which would lead to secondary hyperparathyroidism [27]. Normal intestinal calcium absorption has been reported in a few human diabetics [24,28], whereas low or absent calcium absorption in the duodenum was found in diabetic rats [29]. In a few studies serum I ,25-dihydroxyvitamin D has been measured and was found to be normal [24] or decreased [30].…”
Section: Discussionmentioning
confidence: 99%
“…Of note with reference to the debate over the role of calbindin‐D 9K , knockdown of calbindin‐D 9K in Caco‐2 cells had no effect on prolactin‐stimulated Ca 2+ absorption 130 . In addition, there is evidence from in vivo perfusion experiments that active absorption is present in ileum, where calbindin‐D 9K is very low 10,191,192 ; moreover, changes in absorption can precede changes in calbindin synthesis 193–195 . Taken in conjunction with the knockout mice results, the argument that low calbindin‐D 9K in ileum dictates a paracellular linear component of absorption seems no longer tenable 9,28 …”
Section: Prolactin‐stimulated Ca2+ Absorptionmentioning
confidence: 98%